Amyloid precursor protein Thr668 phosphodependent complexes - Reguengo, Sérgio Paulo Soares (2015)
Alzheimer’s disease has as one of its characteristic hallmarks, deposits of a toxic peptide Aβ, known as senile plaques (SP). The toxic peptide is produced via complex intracellular pathways and cleavage of the Alzheimer’s Amyloid Precursor Protein (APP). Several aspects are key to APP processing. Among them, the proteins that bind to APP and form different complexes, which are functionally relevant. Recent studies have shown that the phosphorylation state of APP itself is determinant with respect to the protein complexes formed. Thus the protein’s phosphorylation state ultimately determines its own fate, the rate of Aβ production and the formation of SPs. It is also noteworthy the patients with Swedish mutation produced 10 times more Aβ. The aim of this thesis is to consider the above mentioned factors, which modulate Aβ production in a unified perspective. That is, to consider how protein phosphorylation affects Aβ production, bearing in mind the phosphorylated state of the protein itself and the complexes that are formed. In order to address these questions, several biological tools have to be available. Hence this thesis set out to prepare the APP Swedish mutations (to produce 10 times more Aβ) on a cDNA which also expressed phosphorylation site mutations on APP Thr668. This was achieved and it was possible to demonstrate that the resulting mutations did in fact produce considerably higher levels of the toxic peptide. Preliminary immunocytochemistry studies allowed for assessment of cellular distribution of the mutants and PP1γ in SHSY5Y cells, and more studies are needed to assess the co-localization of the trimeric protein complex between the APP mutants. PP1γ and Fe65. Therefore additional studies could contribute to a better understanding of the way that Aβ production is influenced by protein complexes regulated by APP phosphorylation.